SECOND‐STAGE TREATMENTS FOR RELATIVE NONRESPONDERS TO COGNITIVE BEHAVIORAL THERAPY (CBT) FOR PANIC DISORDER WITH OR WITHOUT AGORAPHOBIA—CONTINUED CBT VERSUS SSRI: A RANDOMIZED CONTROLLED TRIAL. Issue 5 (10th December 2015) - Payne, Laura A.; White, Kamila S.; Gallagher, Matthew W.; Woods, Scott W.; Shear, M. Katherine; Gorman, Jack M.; Farchione, Todd J.; Barlow, David H.
Abstract : Background: Cognitive behavioral therapy (CBT) and pharmacotherapy are efficacious for the short‐term treatment of panic disorder. Less is known about the efficacy of these therapies for individuals who do not respond fully to short‐term CBT. Method: The current trial is a second‐step stratified randomized design comparing two treatment conditions—selective serotonin reuptake inhibitor (SSRI; paroxetine or citalopram; n = 34) and continued CBT ( n = 24)—in a sample of individuals classified as treatment nonresponders to an initial course of CBT for panic disorder. Participants were randomized to 3 months of treatment and then followed for an additional 9 months. Only treatment responders after 3 months were maintained on the treatment until 12‐month follow‐up. Data analysis focused on panic disorder symptoms and achievement of response status across the first 3 months of treatment. Final follow‐up data are presented descriptively. Results: Participants in the SSRI condition showed significantly lower panic disorder symptoms as compared to continued CBT at 3 months. Results were similar when excluding individuals with comorbid major depression or analyzing the entire intent‐to‐treat sample. Group differences disappeared during 9‐month naturalistic follow‐up, although there was significant attrition and use of nonstudy therapies in both arms. Conclusions: These data suggest greater improvement in panic disorder symptoms when switching to SSRI after failure to fully respond to an initial course of CBT. Future studies should further investigate relapse following treatment discontinuation for nonresponders who became responders. Clinicaltrials.gov Identifier: NCT00000368;https://clinicaltrials.gov/show/NCT00000368